(untitled) (diségno, 2021)
Domenico Iovane’s book reports the results of a research experience focusing the documentation of the amphitheater of the Roman Capua, whose site is today located inside the territory of the municipality of Santa Maria Capua Vetere, province of Caserta. The case study is particularly relevant for the history of Roman Empire architecture and culture; the amphitheater of Capua, built between the end of the 1st and the 2nd century AD, was famous both for its size and for the reputation of the gladiator school that was in that town. Its major and minor axes measured respectively 167 and 134 meters and the cavea could host up to 60,000 people; only the Colosseum in Rome had greater dimensions and capacity. [read more]